COMPARISON OF THE EFFECTIVENESS OF SKIN SWAB AND SKIN SCRAPING TECHNIQUES FOR SCABIES DIAGNOSIS - Ihtiaringtyas, Suci; Susiawan, Lieza Dwianasari; Sari, Octavia Permata; Firinda, Rizma Haidif (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Scabies is a skin disease caused by an infestation of the mite Sarcoptes scabiei var. hominis. This disease often mimics other skin conditions, earning it the nickname